A Semiotic Analysis of Verbal and Visual Signs with Denotative and Connotative Meaning in iPhone 14 Advertisements - I Gede Jody Agastya; Ni Wayan Suastini (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Advertisements are a crucial tool for companies to promote their products, utilizing both verbal and visual signs. This study explores the verbal and visual signs in iPhone 14 advertisements, focusing on their denotative and connotative meanings. The research employs observational methods for data collection and qualitative descriptive methods for analysis, drawing on Saussure's (1983) theory for sign description and Barthes' (1967) theory for meaning interpretation. The findings reveal 12 verbal signs, 8 visual signs, 20 denotative meanings, and 16 connotative meanings across two advertisements. The study highlights how advertisers use verbal and visual signs to create distinct concepts and make their products known to the public